Athletes’ access to, attitudes towards and experiences of help-seeking for mental health: a scoping review - Kirsty R Brown; Mary L Quinton; Grace Tidmarsh; Jennifer Cumming (BMJ Open)
Objectives Athletes have been found to experience a similar prevalence of mental health issues to non-athletes. However, they are subjected to a greater array of barriers to help-seeking for mental health, including sport-specific factors. This scoping review synthesised the literature on athletes’ access to, attitudes towards and experiences of help-seeking for mental health from formal (mental health professionals such as psychiatrists) and semiformal sources (those who are not mental health professionals but are a service provider such as a coach).Design The Joanna Briggs Institute framework and recommendations were used alongside the Preferred Reporting Items for Systematic Reviews and Meta-Analyses-Protocols checklist for scoping reviews. This scoping review was predominantly informed by Arksey and O’Malley’s framework for scoping reviews, supplemented by Levac et al’s additional recommendations. Rickwood and colleagues’ help-seeking frameworks informed the research question, inclusion/exclusion criteria and analysis.Data sources The search terms and synonyms of “athlete” AND “mental health” AND “help-seeking” were searched in PsychINFO, Embase, MEDLINE, APA PsychArticles Full Text, Web of Science Core Collection, Scopus, Sport Discus, CINAHL and Proquest (Education Database, Health & Medical Collection, Nursing & Allied Health database, Psychology Database, Public Health Database, Education Collection, and Medicine & Education). These searches were conducted at three time points between April 2022 and 2024.Eligibility criteria The inclusion and exclusion criteria were initially predetermined and specified in the protocol paper published in BMJ Open. Primary research articles, interventions and systematic reviews that referred to semiformal and formal sources of support were included.Data extraction and synthesis The lead reviewer (KRB) screened all titles and abstracts, and full texts, and extracted data from all included studies. A second reviewer was involved in screening and extracting 20%–30% of studies at each stage. Findings were synthesised descriptively (eg, study population, data collection method and location of studies) and by content (eg, access, attitudes and experiences, sources of support, use of theory and the validity of quantitative measures used).Results After screening 4954 titles and abstracts and 275 full texts in Covidence, 104 papers were included in the review. This comprised of 87 primary research articles, 13 interventions and 4 systematic reviews. Most of the primary articles and interventions were published in the USA (50%). 49.4% of the primary articles used quantitative methods, 34.5% used qualitative methods and 16.1% used mixed methods. Attitudes towards mental health help-seeking were investigated in 78.8% of the included studies, experiences of help-seeking in 53.8% and access to sources of support in 31.7% of studies. Of the primary articles and interventions, formal sources were investigated in 55% of studies, semiformal sources in 2% and both in 26% of studies.Conclusions This scoping review of 104 papers showed the benefit of using help-seeking frameworks to shape and analyse a review. Analysing the results using these frameworks provided a novel contribution to the literature, showing where the athlete help-seeking literature base is currently focused and identified gaps for further research. For example, there is a need for further research on athletes in less developed nations, more qualitative and mixed methods studies, and further research on athletes’ access to mental health support and their interactions with semiformal sources. The results have applied implications in public health and sport by highlighting the different factors that impact athlete help-seeking, and therefore areas where they require support.